Diabetes Self-Management: Using the Colored Eco-Genetic Relationship Map to Assess Social Support. Issue 2 (March 2015) - Wallace, Andrea S.; Driessnack, Martha; Bohr, Nicole; Tripp-Reimer, Toni
Abstract : Background: The positive association between individual social support and diabetes health outcomes is well established. However, most tools for assessing social support are highly structured and are rarely used in clinical settings and/or clinical outcomes research. A novel tool that has been shown to engage patients in the identification and use of their social networks is the Colored Eco-Genetic Relationship Map (CEGRM). Objective: The purpose of this pilot study was to explore the feasibility of using the CEGRM adapted for eliciting information about how individuals with diabetes use their social networks to support their self-management efforts. Methods: A sample of 18 adult patients with diabetes completed the newly created diabetes-CEGRM (D-CEGRM) alongside structured questions regarding social support for diabetes self-management. Results: Whereas structured questions elicited information about participants' use of social networks, the D-CEGRM expanded on answers from structured questions by identifying both positive and negative aspects of social support, additional individual and community-based resources, and nuanced interpersonal information about the individuals involved. Discussion: The D-CEGRM appears to be feasible and useful in assessing the social networks of adults with diabetes and how they are used to support tasks related to self-management. The information elicited by completing the D-CEGRM expanded on information collected through structured questions about social support in a way that might better address research questions and inform clinical decision making. Abstract : Supplemental Digital Content is available in the text